A rubber adhesion accelerator and preparation method thereof

By using the combination of silane coupling agent KH560, a modifier doped whisker-adjusting modifier, a stability-resistant supplement and chitosan liquid as a rubber adhesion promoter, the problem of difficult balance of the strength, elongation and wear resistance of rubber products in the prior art is solved, and the high performance stability of rubber products under cold-heat cycle aging and corrosion resistance conditions is achieved.

CN119307008BActive Publication Date: 2025-03-07DALIAN AIBESI CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411833612.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing rubber adhesion accelerators have no obvious effect in improving the strength, elongation and wear resistance of rubber products, and the product stability is reduced under the conditions of cold-heat cycle aging and corrosion resistance.

Method used

The combination of silane coupling agent KH560, a modifier doped whisker-adjusting modifier, a stability-resistant supplement and chitosan liquid is used as a rubber bonding promoter, and the adhesion effect and stability are enhanced through specific material mass ratios and preparation methods.

Benefits of technology

The strength, elongation and wear resistance of rubber products are significantly improved, especially under cold-heat cycle aging and corrosion resistance, the product has excellent performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of rubber adhesion, and in particular to a rubber adhesion promoter and a preparation method thereof, wherein the adhesion promoter comprises a silane coupling agent KH560, a modifier prepared by doping whiskers, a resistance and stability supplement agent and a chitosan solution; wherein the mass ratio of the silane coupling agent KH560, the modifier prepared by doping whiskers, the resistance and stability supplement agent and the chitosan solution is 2: (5-7): (3-4): 9. The rubber adhesion promoter of the present invention adopts the silane coupling agent KH560 in combination with the modifier prepared by doping whiskers and the resistance and stability supplement agent, and the chitosan solution is added for blending, and the modifier prepared by doping whiskers and the resistance and stability supplement agent are used for coordination, and the adhesion promoter obtained by the synergistic combination enhances the coordination of the strength, elongation and wear resistance of the product in the rubber system, and the rubber product has excellent performance stability under cold-heat cycle aging and corrosion resistance conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber bonding, and in particular to a rubber bonding accelerator and a preparation method thereof. Background Art

[0002] Rubber products refer to the activities of producing various rubber products using natural and synthetic rubber as raw materials, and also include rubber products reproduced from waste rubber. The output of synthetic rubber has greatly exceeded that of natural rubber. Fiber fillers are often added to rubber products to enhance product performance. However, fiber fillers are not easy to disperse evenly in the rubber system and have poor adhesion to rubber. The final product quality distribution is uneven and the overall performance is not ideal. Therefore, adhesion promoters are added to improve the mixing effect of rubber and improve the dispersion and adhesion of fiber fillers in the rubber compound.

[0003] Existing adhesion promoters use simple raw materials, and have little effect on improving the strength and elongation at break of rubber products. It is difficult to improve the strength, elongation and wear resistance of the products in a balanced manner. In addition, the stability of rubber products is reduced under cold-heat cycle aging and corrosion resistance conditions, which limits the use efficiency of adhesion promoters. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a rubber adhesion promoter and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The invention provides a rubber adhesion promoter, which comprises a silane coupling agent KH560, a modifier prepared by doping with a whisker, a resistant and stable compensating agent and a chitosan solution; wherein the mass ratio of the silane coupling agent KH560, the modifier prepared by doping with a whisker, the resistant and stable compensating agent and the chitosan solution is 2: (5-7): (3-4): 9;

[0007] The preparation method of the modifier prepared by doping whiskers is:

[0008] S01: Stir the calcium sulfate whiskers thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry;

[0009] The dried calcium sulfate whiskers are irradiated in a plasma box at a power of 350-400 W for 20 minutes, and an irradiated calcium sulfate whisker agent is obtained after the irradiation is completed.

[0010] S02: Mix nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose in a weight ratio of 3: (5-7): 1 to obtain nano titanium dioxide liquid;

[0011] Add 2-5 parts of nano titanium dioxide liquid and 1-3 parts of nano silica sol into 5-8 parts of lanthanum chloride solution, then add 3-5 parts of cobalt hydroxide and stir thoroughly to obtain a nano titanium dioxide modifier;

[0012] S03: immersing the irradiated calcium sulfate whisker agent into a nano-titanium dioxide modifier with a total amount of 3 to 5 times the total amount of the irradiated calcium sulfate whisker agent, immersing and stirring, and after the immersion is completed, filtering and drying to obtain a modifier prepared by doping whiskers;

[0013] The preparation method of the stable tonic agent is as follows:

[0014] S11: heat treating the flake graphene at 215-225°C for 10-15 min, then heating to 330-340°C at a rate of 1-3°C / min, keeping the temperature for 5 min, and finally air cooling to room temperature;

[0015] S12: Preparation of modified solution:

[0016] 1-3 parts of stearic acid and 2-3 parts of hydroxyapatite are added to 4-6 parts of sodium dodecylbenzene sulfonate solution, and then 2-3 parts of silane coupling agent KH550 are added to fully mix to obtain a modified solution;

[0017] The flake graphene of S11 and the modified liquid are subjected to ultrasonic treatment in a weight ratio of 2:(5-6), and the ultrasonic treatment is terminated to obtain a modified flake graphene liquid;

[0018] S13: The modified flake graphene liquid and the stabilizing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a stabilizing agent.

[0019] Preferably, the chitosan solution is a chitosan solution with a mass fraction of 3-5%; the mass ratio of the silane coupling agent KH560, the modifier prepared by doping whiskers, the endurance and stability supplement agent and the chitosan solution is 2:6:3.5:9.

[0020] Preferably, the stirring speed of the immersion stirring treatment is 550-650 r / min, and the stirring time is 30-40 min.

[0021] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-6%.

[0022] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-6%; the ultrasonic power of the ultrasonic treatment is 500-600 W, and the ultrasonic time is 20-30 min.

[0023] Preferably, the preparation method of the replenishing and adjusting stabilizer is:

[0024] The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina;

[0025] 2-5 parts of yttrium-doped nano-alumina, 1-3 parts of sodium lignin sulfonate, 5-7 parts of dopamine hydrochloride solution and 2-4 parts of silicon nitride powder are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a replenishing stabilizer.

[0026] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the yttrium nitrate solution is 3-6%.

[0027] The present invention also provides a method for preparing a rubber adhesion promoter, comprising the following steps: mixing silane coupling agent KH560, a modifier prepared by doping whiskers, a stable compensating agent and chitosan liquid according to a proportion to obtain the rubber adhesion promoter.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The rubber adhesion promoter of the present invention adopts silane coupling agent KH560 in combination with a modifier prepared by doping whiskers and a stable and effective agent, and chitosan liquid is added for blending. The modifier prepared by doping whiskers and the stable and effective agent are coordinated to obtain an adhesion promoter that enhances the coordination of strength, elongation and wear resistance of the product in the rubber system, and the rubber product has excellent performance stability under cold-heat cycle aging and corrosion resistance conditions;

[0030] 2. The modifier doped with whiskers is prepared by treating calcium sulfate whiskers with hydrogen peroxide solution and then irradiating with plasma to optimize the active performance of the product. At the same time, nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose are blended and coordinated to obtain nano titanium dioxide liquid, and then nano silica sol, lanthanum chloride solution and cobalt hydroxide are blended. The raw materials are coordinated and synergized to obtain the nano titanium dioxide modifier, which is then coordinated with calcium sulfate whiskers. The nano titanium dioxide modifier is blended with the whisker structure of calcium sulfate whiskers, and the whisker-like structure of whiskers is used to coordinate with raw materials such as nano titanium dioxide. The coordination of system performance is enhanced through the synergy between the raw materials, and the cold-heat cycle aging and corrosion resistance stability of the product are optimized;

[0031] 3. The stable and effective agent uses flake graphene to undergo heat treatment at 215-225°C for 10-15 minutes, then heats up to 330-340°C at a rate of 1-3°C / min, and keeps warm for 5 minutes. The active performance of flake graphene is optimized through heat improvement treatment, and at the same time, a modified liquid is used for improvement treatment. Stearic acid, hydroxyapatite, sodium dodecylbenzene sulfonate solution and silane coupling agent KH550 in the modified liquid are blended. The raw materials in the modified liquid cooperate with each other to strengthen and coordinate the flake graphene structure system. At the same time, the added stabilizer further coordinates and coordinates the flake graphene, and the performance of the product is further improved;

[0032] 4. The nano-alumina in the replenishing and stabilizing agent is combined with yttrium nitrate solution, and the nano-alumina is improved by blending the yttrium nitrate solution to obtain yttrium-doped nano-alumina, which is then further blended and coordinated with sodium lignin sulfonate, dopamine hydrochloride solution and silicon nitride powder. The replenishing and stabilizing agent thus obtained can better improve the graphene system, and the stabilizing and stabilizing agent thus obtained can be better coordinated with the modifier formulated with the doped whisker, and the performance of the product is further improved. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A rubber adhesion promoter of the present embodiment comprises a silane coupling agent KH560, a modifier prepared by doping with a crystal whisker, a stabilizing agent and a chitosan solution; wherein the mass ratio of the silane coupling agent KH560, the modifier prepared by doping with a crystal whisker, the stabilizing agent and the chitosan solution is 2: (5-7): (3-4): 9; and the preparation method of the modifier prepared by doping with a crystal whisker is as follows:

[0035] S01: Stir the calcium sulfate whiskers thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry;

[0036] The dried calcium sulfate whiskers are irradiated in a plasma box at a power of 350-400 W for 20 minutes, and an irradiated calcium sulfate whisker agent is obtained after the irradiation is completed.

[0037] S02: Mix nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose in a weight ratio of 3: (5-7): 1 to obtain nano titanium dioxide liquid;

[0038] Add 2-5 parts of nano titanium dioxide liquid and 1-3 parts of nano silica sol into 5-8 parts of lanthanum chloride solution, then add 3-5 parts of cobalt hydroxide and stir thoroughly to obtain a nano titanium dioxide modifier;

[0039] S03: immersing the irradiated calcium sulfate whisker agent into a nano titanium dioxide modifier with a total amount of 3 to 5 times the total amount of the irradiated calcium sulfate whisker agent, immersing and stirring, and after the immersion is completed, filtering and drying are performed to obtain a modifier prepared by doping whiskers; the preparation method of the stable compensating agent is:

[0040] S11: heat treating the flake graphene at 215-225°C for 10-15 min, then heating to 330-340°C at a rate of 1-3°C / min, keeping the temperature for 5 min, and finally air cooling to room temperature;

[0041] S12: Preparation of modified solution:

[0042] 1-3 parts of stearic acid and 2-3 parts of hydroxyapatite are added to 4-6 parts of sodium dodecylbenzene sulfonate solution, and then 2-3 parts of silane coupling agent KH550 are added to fully mix to obtain a modified solution;

[0043] The flake graphene of S11 and the modified liquid are subjected to ultrasonic treatment in a weight ratio of 2:(5-6), and the ultrasonic treatment is terminated to obtain a modified flake graphene liquid;

[0044] S13: The modified flake graphene liquid and the stabilizing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a stabilizing agent.

[0045] The chitosan solution of this embodiment is a chitosan solution with a mass fraction of 3-5%; the mass ratio of the silane coupling agent KH560, the modifier prepared by doping whiskers, the stability-replenishing agent and the chitosan solution is 2:6:3.5:9.

[0046] The stirring speed of the immersion stirring process in this embodiment is 550-650 r / min, and the stirring time is 30-40 min.

[0047] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 4-6%.

[0048] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 4-6%; the ultrasonic power of the ultrasonic treatment is 500-600W, and the ultrasonic time is 20-30min.

[0049] The preparation method of the supplementary stabilizing agent of this embodiment is:

[0050] The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina;

[0051] 2-5 parts of yttrium-doped nano-alumina, 1-3 parts of sodium lignin sulfonate, 5-7 parts of dopamine hydrochloride solution and 2-4 parts of silicon nitride powder are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a replenishing stabilizer.

[0052] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%; the mass fraction of the yttrium nitrate solution is 3-6%.

[0053] The preparation method of a rubber adhesion promoter of the present embodiment comprises the following steps: mixing a silane coupling agent KH560, a modifier prepared by doping whiskers, a stable compensating agent and a chitosan solution in a proportion to obtain the rubber adhesion promoter of the present invention.

[0054] Example 1

[0055] A rubber adhesion promoter of this embodiment comprises a silane coupling agent KH560, a modifier prepared by doping with whiskers, a resistant and stable compensating agent and a chitosan solution; wherein the mass ratio of the silane coupling agent KH560, the modifier prepared by doping with whiskers, the resistant and stable compensating agent and the chitosan solution is 2:5:3:9.

[0056] The chitosan solution in this embodiment is a chitosan solution with a mass fraction of 3%.

[0057] The preparation method of the modifier prepared by doping whiskers in this embodiment is:

[0058] S01: Stir the calcium sulfate whiskers thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry;

[0059] The dried calcium sulfate whiskers were irradiated in a plasma box at a power of 350 W for 20 minutes to obtain an irradiated calcium sulfate whisker agent;

[0060] S02: mixing nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose in a weight ratio of 3:5:1 to obtain nano titanium dioxide liquid;

[0061] Add 2 parts of nano titanium dioxide liquid and 1 part of nano silica sol into 5 parts of lanthanum chloride solution, then add 3-5 parts of cobalt hydroxide and stir thoroughly to obtain nano titanium dioxide modifier;

[0062] S03: immersing the irradiated calcium sulfate whisker agent into a nano titanium dioxide modifier with a total amount that is three times the total amount of the irradiated calcium sulfate whisker agent, and stirring the mixture. After the immersion is completed, the mixture is filtered and dried to obtain a modifier prepared by doping whiskers.

[0063] The stirring speed of the immersion stirring process in this embodiment is 550 r / min, and the stirring time is 30 min.

[0064] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 4%.

[0065] The preparation method of the stable tonic agent of this embodiment is:

[0066] S11: The graphene flakes were first heat treated at 215°C for 10 min, then heated to 330°C at a rate of 1°C / min, kept at that temperature for 5 min, and finally air-cooled to room temperature;

[0067] S12: Preparation of modified solution:

[0068] 1 part of stearic acid and 2 parts of hydroxyapatite are added to 4 parts of sodium dodecylbenzene sulfonate solution, and then 2 parts of silane coupling agent KH550 are added and mixed to obtain a modified solution;

[0069] The flake graphene of S11 and the modified liquid are ultrasonically treated in a weight ratio of 2:5, and the ultrasonic treatment is terminated to obtain a modified flake graphene liquid;

[0070] S13: The modified flake graphene liquid and the stabilizing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a stabilizing agent.

[0071] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 4%; the ultrasonic power of the ultrasonic treatment is 500 W, and the ultrasonic time is 20 min.

[0072] The preparation method of the supplementary stabilizing agent of this embodiment is:

[0073] The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina;

[0074] 2 parts of yttrium-doped nano-alumina, 1 part of sodium lignin sulfonate, 5 parts of dopamine hydrochloride solution and 2 parts of silicon nitride powder were mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a replenishing stabilizer.

[0075] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%; the mass fraction of the yttrium nitrate solution is 3%.

[0076] The preparation method of a rubber adhesion promoter of the present embodiment comprises the following steps: mixing a silane coupling agent KH560, a modifier prepared by doping whiskers, a stable compensating agent and a chitosan solution in a proportion to obtain the rubber adhesion promoter of the present invention.

[0077] Example 2

[0078] A rubber adhesion promoter of this embodiment comprises a silane coupling agent KH560, a modifier prepared by doping with whiskers, a resistant and stable compensating agent and a chitosan solution; wherein the mass ratio of the silane coupling agent KH560, the modifier prepared by doping with whiskers, the resistant and stable compensating agent and the chitosan solution is 2:7:4:9.

[0079] The chitosan solution in this embodiment is a chitosan solution with a mass fraction of 5%.

[0080] The preparation method of the modifier prepared by doping whiskers in this embodiment is:

[0081] S01: Stir the calcium sulfate whiskers thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry;

[0082] The dried calcium sulfate whiskers are irradiated in a plasma box at a power of 400 W for 20 minutes, and an irradiated calcium sulfate whisker agent is obtained after the irradiation is completed.

[0083] S02: mixing nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose in a weight ratio of 3:7:1 to obtain nano titanium dioxide liquid;

[0084] Add 5 parts of nano titanium dioxide liquid and 3 parts of nano silica sol into 8 parts of lanthanum chloride solution, then add 5 parts of cobalt hydroxide and stir thoroughly to obtain a nano titanium dioxide modifier;

[0085] S03: immersing the irradiated calcium sulfate whisker agent into a nano-titanium dioxide modifier with a total amount of 5 times the total amount of the irradiated calcium sulfate whisker agent, immersing and stirring, and after the immersion is completed, filtering and drying are performed to obtain a modifier prepared by doping whiskers.

[0086] The stirring speed of the immersion stirring process in this embodiment is 650 r / min, and the stirring time is 40 min.

[0087] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 6%.

[0088] The preparation method of the stable tonic agent of this embodiment is:

[0089] S11: The graphene flakes were first heat treated at 225°C for 15 min, then heated to 340°C at a rate of 3°C / min, kept at that temperature for 5 min, and finally air-cooled to room temperature;

[0090] S12: Preparation of modified solution:

[0091] 3 parts of stearic acid and 3 parts of hydroxyapatite are added to 6 parts of sodium dodecylbenzene sulfonate solution, and then 3 parts of silane coupling agent KH550 are added and mixed to obtain a modified solution;

[0092] The flake graphene of S11 and the modified liquid are ultrasonically treated in a weight ratio of 2:6, and the ultrasonic treatment is terminated to obtain a modified flake graphene liquid;

[0093] S13: The modified flake graphene liquid and the stabilizing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a stabilizing agent.

[0094] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 6%; the ultrasonic power of the ultrasonic treatment is 600 W, and the ultrasonic time is 30 min.

[0095] The preparation method of the supplementary stabilizing agent of this embodiment is:

[0096] The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina;

[0097] 5 parts of yttrium-doped nano-alumina, 3 parts of sodium lignin sulfonate, 7 parts of dopamine hydrochloride solution and 4 parts of silicon nitride powder were mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a supplementary stabilizer.

[0098] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%; the mass fraction of the yttrium nitrate solution is 6%.

[0099] The preparation method of a rubber adhesion promoter of the present embodiment comprises the following steps: mixing a silane coupling agent KH560, a modifier prepared by doping whiskers, a stable compensating agent and a chitosan solution in a proportion to obtain the rubber adhesion promoter of the present invention.

[0100] Example 3

[0101] A rubber adhesion promoter of the present embodiment comprises a silane coupling agent KH560, a modifier prepared by doping with a whisker, a resistant and stable compensating agent and a chitosan solution; the chitosan solution is a chitosan solution with a mass fraction of 4%; the mass ratio of the silane coupling agent KH560, the modifier prepared by doping with a whisker, the resistant and stable compensating agent and the chitosan solution is 2:6:3.5:9.

[0102] The preparation method of the modifier prepared by doping whiskers in this embodiment is:

[0103] S01: Stir the calcium sulfate whiskers thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry;

[0104] The dried calcium sulfate whiskers were irradiated in a plasma box at an irradiation power of 370 W for 20 minutes, and an irradiated calcium sulfate whisker agent was obtained after the irradiation was completed.

[0105] S02: mixing nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose in a weight ratio of 3:6:1 to obtain nano titanium dioxide liquid;

[0106] 3.5 parts of nano titanium dioxide liquid and 2 parts of nano silica sol are added to 6.5 parts of lanthanum chloride solution, and then 4 parts of cobalt hydroxide are added and stirred to obtain a nano titanium dioxide modifier;

[0107] S03: Immerse the irradiated calcium sulfate whisker agent into a nano titanium dioxide modifier with a total amount of 4 times the total amount of the irradiated calcium sulfate whisker agent, immerse and stir, and after the immersion is completed, filter and dry to obtain a modifier prepared by doping whiskers.

[0108] The stirring speed of the immersion stirring process in this embodiment is 600 r / min, and the stirring time is 35 min.

[0109] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 5%.

[0110] The preparation method of the stable tonic agent of this embodiment is:

[0111] S11: The graphene flakes were first heat treated at 220°C for 12.5 min, then heated to 335°C at a rate of 2°C / min, kept at that temperature for 5 min, and finally air-cooled to room temperature;

[0112] S12: Preparation of modified solution:

[0113] 2 parts of stearic acid and 2.5 parts of hydroxyapatite are added to 5 parts of sodium dodecylbenzene sulfonate solution, and then 2.5 parts of silane coupling agent KH550 are added and mixed to obtain a modified solution;

[0114] The flake graphene of S11 and the modified liquid are ultrasonically treated in a weight ratio of 2:5.5, and the ultrasonic treatment is terminated to obtain a modified flake graphene liquid;

[0115] S13: The modified flake graphene liquid and the stabilizing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a stabilizing agent.

[0116] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 5%; the ultrasonic power of the ultrasonic treatment is 550W, and the ultrasonic time is 25min.

[0117] The preparation method of the supplementary stabilizing agent of this embodiment is:

[0118] The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina;

[0119] 3.5 parts of yttrium-doped nano-alumina, 2 parts of sodium lignin sulfonate, 6 parts of dopamine hydrochloride solution and 3 parts of silicon nitride powder were mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a replenishing stabilizer.

[0120] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%; the mass fraction of the yttrium nitrate solution is 4.5%.

[0121] The preparation method of a rubber adhesion promoter of the present embodiment comprises the following steps: mixing a silane coupling agent KH560, a modifier prepared by doping whiskers, a stable compensating agent and a chitosan solution in a proportion to obtain the rubber adhesion promoter of the present invention.

[0122] Comparative Example 1

[0123] The difference from Example 3 is that no modifier for doped whisker formulation is added.

[0124] Comparative Example 2

[0125] The difference from Example 3 is that no irradiated calcium sulfate whisker agent is added in the preparation of the modifier for doping whiskers.

[0126] Comparative Example 3

[0127] The difference from Example 3 is that the S01 step is not used in the preparation of the irradiated calcium sulfate whisker agent.

[0128] Comparative Example 4

[0129] The difference from Example 3 is that no nano titanium dioxide modifier is added.

[0130] Comparative Example 5

[0131] The difference from Example 3 is that no nano titanium dioxide liquid is added to the nano titanium dioxide modifier.

[0132] Comparative Example 6

[0133] The difference from Example 3 is that the nano titanium dioxide liquid is directly replaced by nano titanium dioxide.

[0134] Comparative Example 7

[0135] The difference from Example 3 is that no cobalt hydroxide or lanthanum chloride solution is added in the preparation of the nano-titanium dioxide modifier, and water is used instead.

[0136] Comparative Example 8

[0137] The difference from Example 3 is that no stable tonic agent is added.

[0138] Comparative Example 9

[0139] The difference from Example 3 is that the S11 step is not used in the preparation of the stable tonic agent.

[0140] Comparative Example 10

[0141] The difference from Example 3 is that no modifying liquid treatment was used in the preparation of the stable tonic agent.

[0142] Comparative Example 11

[0143] The difference from Example 3 is that hydroxyapatite and silane coupling agent KH550 are not added to the modified liquid.

[0144] Comparative Example 12

[0145] The difference from Example 3 is that no stabilizer was used in the preparation of the stable tonic agent.

[0146] 100 parts of natural rubber, 15 parts of styrene-butadiene rubber, 5 parts of antioxidant 4020, 3 parts of carbon black, 3 parts of zinc oxide, 2 parts of sulfur, 2 parts of stearic acid and 10 parts of carbon fiber filler were subjected to the prior art banburying and vulcanization process to obtain a control group rubber base material;

[0147] The products of Examples 1-3 and Comparative Examples 1-12 were added to the rubber base material with 5 parts by weight, and the rubber base materials of Examples 1-3 and Comparative Examples 1-12 were prepared according to the above method. At the same time, the rubber base materials of the control group and the rubber base materials of Examples 1-3 and Comparative Examples 1-12 were placed at -5°C for 12 hours, then at 65°C for 12 hours, and placed under 2% hydrochloric acid mist conditions for 12 hours. The above is one cycle, and the cycle test is repeated 10 times to test the cold and heat resistance and acid corrosion stability of the products, and the product performance of Examples 1-3 and Comparative Examples 1-12 is tested. The test results are as follows:

[0148]

[0149] It can be seen from Comparative Examples 1 to 12, the Control Group and Examples 1 to 3 that;

[0150] The product of Example 3 has excellent tensile strength, tensile elongation and wear resistance, and the product performance can be improved in a coordinated manner, and the product has significant performance stability under cold, heat, acid and corrosion conditions;

[0151] The present invention does not add a modifier for doping whiskers and does not add a stabilizer. The performance effect of the product is significantly deteriorated. The two are used in combination to achieve synergy, and the performance effect of the product is obvious.

[0152] The performance of the products tended to deteriorate when no irradiated calcium sulfate whisker agent was added to the preparation of the modifier for doped whiskers, no S01 treatment was used in the preparation of the irradiated calcium sulfate whisker agent, no nano titanium dioxide modifier was added, nano titanium dioxide liquid was not added to the nano titanium dioxide modifier, nano titanium dioxide liquid was directly replaced by nano titanium dioxide, no cobalt hydroxide was added to the preparation of the nano titanium dioxide modifier, and lanthanum chloride solution was replaced by water;

[0153] At the same time, the performance of the product without adding the irradiated calcium sulfate whisker agent deteriorated significantly, and the performance of the product without adding the nano titanium dioxide modifier also showed a trend of deterioration. Only the modifier prepared by the doped whisker obtained by the method of the present invention had the most significant performance effect of the product.

[0154] The performance of the products showed a trend of deterioration when the S11 step was not used in the preparation of the resistant and stable supplementary agent, the modifying liquid was not used in the preparation of the resistant and stable supplementary agent, the hydroxyapatite and silane coupling agent KH550 were not added to the modifying liquid, and the supplementary and stabilizing agent was not used in the preparation of the resistant and stable supplementary agent. The performance of the products deteriorated significantly when the supplementary and stabilizing agent was not used in the preparation of the resistant and stable supplementary agent.

[0155] The modified liquid obtained by the specific method of the present invention is combined with a supplementary stabilizing agent to obtain the present invention's stabilizing agent, and the product performance effect is the most significant. Other methods used instead are not as obvious as the effect of the present invention.

[0156] Since the performance of the product is greatly changed by the stabilizer, further research is conducted on this:

[0157] The preparation method of the supplementary stabilizer is as follows:

[0158] The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina;

[0159] 3.5 parts of yttrium-doped nano-alumina, 2 parts of sodium lignin sulfonate, 6 parts of dopamine hydrochloride solution and 3 parts of silicon nitride powder were mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a replenishing stabilizer.

[0160] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%; the mass fraction of the yttrium nitrate solution is 4.5%.

[0161] Experimental Example 1

[0162] The only difference from Example 3 is that silicon nitride powder is not added in the preparation of the supplementary stabilizing agent.

[0163] Experimental Example 2

[0164] The only difference from Example 3 is that yttrium-doped nano-alumina is not added in the preparation of the supplementary stabilizing agent.

[0165] Experimental Example 3

[0166] The only difference from Example 3 is that the yttrium-doped nano-alumina is directly replaced by the nano-alumina raw material.

[0167] Experimental Example 4

[0168] The only difference from Example 3 is that the dopamine hydrochloride solution is replaced by water.

[0169] Experimental Example 5

[0170] The only difference from Example 3 is that sodium lignin sulfonate is not added in the preparation of the supplementary stabilizer.

[0171]

[0172] It can be seen from Experimental Examples 1-5 that yttrium-doped nano-alumina is not added in the preparation of the replenishing and stabilizing agent, and the performance deterioration of the product has the greatest impact trend in the preparation of the replenishing and stabilizing agent, followed by not adding silicon nitride powder in the preparation of the replenishing and stabilizing agent. At the same time, yttrium-doped nano-alumina is not added to the product, yttrium-doped nano-alumina is directly replaced by nano-alumina raw material, dopamine hydrochloride solution is replaced by water, and sodium lignin sulfonate is not added in the preparation of the replenishing and stabilizing agent. The performance of the products all tends to deteriorate. Only the performance effect of the products prepared by using the specific raw materials of the present invention is the most significant, and the effects of other methods are not as obvious as those of the present invention.

[0173] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0174] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A rubber adhesion promoter, characterized in that: The adhesion promoter comprises a silane coupling agent KH560, a modifier prepared by doping with a whisker, a stabilizer and a chitosan solution; wherein the mass ratio of the silane coupling agent KH560, the modifier prepared by doping with a whisker, the stabilizer and the chitosan solution is 2: (5-7): (3-4): 9; The preparation method of the modifier prepared by doping whiskers is: S01: Stir the calcium sulfate whiskers thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry; The dried calcium sulfate whiskers are irradiated in a plasma box at a power of 350-400 W for 20 minutes, and an irradiated calcium sulfate whisker agent is obtained after the irradiation is completed. S02: Mix nano titanium dioxide, sodium silicate solution and sodium carboxymethyl cellulose in a weight ratio of 3: (5-7): 1 to obtain nano titanium dioxide liquid; Add 2-5 parts of nano titanium dioxide liquid and 1-3 parts of nano silica sol into 5-8 parts of lanthanum chloride solution, then add 3-5 parts of cobalt hydroxide and stir thoroughly to obtain a nano titanium dioxide modifier; S03: immersing the irradiated calcium sulfate whisker agent into a nano-titanium dioxide modifier with a total amount of 3 to 5 times the total amount of the irradiated calcium sulfate whisker agent, immersing and stirring, and after the immersion is completed, filtering and drying to obtain a modifier prepared by doping whiskers; The preparation method of the stable tonic agent is as follows: S11: heat treating the flake graphene at 215-225°C for 10-15 min, then heating to 330-340°C at a rate of 1-3°C / min, keeping the temperature for 5 min, and finally air cooling to room temperature; S12: Preparation of modified solution: 1-3 parts of stearic acid and 2-3 parts of hydroxyapatite are added to 4-6 parts of sodium dodecylbenzene sulfonate solution, and then 2-3 parts of silane coupling agent KH550 are added to fully mix to obtain a modified solution; The flake graphene of S11 and the modified liquid are subjected to ultrasonic treatment in a weight ratio of 2:(5-6), and the ultrasonic treatment is terminated to obtain a modified flake graphene liquid; S13: The modified flake graphene liquid and the compensating and stabilizing agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a compensating and stabilizing agent. The preparation method of the compensating and stabilizing agent is as follows: The nano-alumina and yttrium nitrate solution are stirred and mixed thoroughly in a weight ratio of 2:5, and then filtered and dried to obtain yttrium-doped nano-alumina; 2-5 parts of yttrium-doped nano-alumina, 1-3 parts of sodium lignin sulfonate, 5-7 parts of dopamine hydrochloride solution and 2-4 parts of silicon nitride powder are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a replenishing stabilizer.

2. A rubber adhesion promoter according to claim 1, characterized in that: The chitosan solution is a chitosan solution with a mass fraction of 3-5%; the mass ratio of the silane coupling agent KH560, the modifier prepared by doping whiskers, the endurance and stability supplement agent and the chitosan solution is 2:6:3.5:

9.

3. A rubber adhesion promoter according to claim 1, characterized in that: The stirring speed of the immersion stirring process is 550-650 r / min, and the stirring time is 30-40 min.

4. A rubber adhesion promoter according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-6%.

5. A rubber adhesion promoter according to claim 1, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 4-6%; the ultrasonic power of the ultrasonic treatment is 500-600W, and the ultrasonic time is 20-30min.

6. A rubber adhesion promoter according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the yttrium nitrate solution is 3-6%.

7. A method for preparing a rubber adhesion promoter according to any one of claims 1 to 6, characterized in that: The following steps are involved: The silane coupling agent KH560, the modifier prepared by doping the whisker, the resistant and stable compensating agent and the chitosan solution are mixed in proportion to obtain the rubber adhesion promoter.

Citation Information

Patent Citations

  • High-temperature-resistant heat-conducting insulating paint and preparation method thereof

    CN117925055A

  • Preparation method and application of diatomite and zinc oxide composite high-density rubber material

    CN118374068A